SYSTEM ANALYSIS OF THE INTEGRATION PURPOSES OF CORPORATE STRUCTURES - A.H. Galiyeva; A.N. Toksanova; G.S. Ukubassova; M.T. Kulubekov; Zh.N. Sadu (Academic Journal of Physical and Chemical Sciences, 2019)
The purpose of the article is to analyze the socio-economic goals of integration of corporate structures to determine the feasibility of their creation. The relevance of the work is due to the need for a comprehensive assessment of the feasibility of integrating financial and industrial structures in terms of the socio-economic development of society as a whole, as well as coordinating the economic interests of the integrated structures. The paper considers the criteria for evaluating and selecting projects for creating corporate structures. In addition, the article identifies the main directions for conducting a systematic study of the processes of integration and the results of integrated corporate structures. As the main integrative quality, the authors indicate the existence of a common goal of the economic system of the national economy. At the same time, the authors define the overall economic goal at the macroeconomic level as satisfying the socially necessary level of solvent demand of all segments of the population with a systematic reduction of socially necessary costs per unit of beneficial effect. The main conclusions and practical recommendations developed in the framework of the study can be used as a methodological basis for further deepening research on this issue.